A new pathogenic variant in the TRIOBP associated with profound deafness is remediable with cochlear implantation - Tekin, Ahmet Mahmut; de Ceulaer, Geert; Govaerts, Paul; Bayazıt, Yıldırım; Wuyts, Wim; van de Heyning, Paul; Topsakal, Vedat (Karger, 2021)
Background and Objectives: A rare type of nonsyndromic autosomal recessive hereditary hearing loss is caused by pathogenic mutations in the TRIOBP gene mostly involving exons 6 and 7. These mutations cause hearing loss originating from dysfunction of sensory inner ear hair cells. Of all the affected siblings, 2 brothers and 1 sister, part of an Afghan family, were referred to our clinic for diagnostic workup and candidacy selection for cochlear implantation (CI). Methods: Molecular analysis showed a homozygous c.1342C > T p. (Arg448*) pathogenic variant in exon 7 of the TRIOBP gene (reference sequence NM_001039141.2) in all 3 affected siblings. Clinical audiometry demonstrated profound sensorineural hearing loss in all 3 affected siblings (2 males and 1 female), and they were implanted unilaterally. Results: One month after activation, the pure-tone averages with the CI processor were between 30 and 23 dBHL. Ten months after the first activation of the implant, open-set speech audiometry test could be performed for the first time in the 2 younger CI recipients (S5 and S9), and they could identify up to a maximum 77% phonemes correctly. The oldest brother (S12) could not yet perform open-set speech audiometry at that moment. Conclusions: Implant outcomes are better with normal inner ear anatomy in general. The earlier congenital patients are implanted, the better their outcomes. Here, we demonstrate both statements are true in a homozygous c.1342C > T p. (Arg448*) pathogenic variant in the TRIOBP gene in all 3 affected siblings.
Keywords: Sensorineural Hearing Loss; Cochlear Implantation; Hereditary Hearing Loss; Genetic Deafness; Hereditary